Pelatihan Media Pembelajaran Dengan Microsoft Powerpoint Pada Siswa SMK YAPIM - Robiatul Adawiyah; Fitriana Harahap; Nidia Enjelita saragih; Siti Nurhidayah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
The Tridharma of Higher Education contains three important points, namely education, research and community service. Community service on this occasion was carried out with partners from Yapim Mabar Vocational School. In the era of digitalization, student creativity is very important, so it is necessary to provide computer programs such as Ms. Office, including Microsoft Power Point. There is a need for training on computer applications related to Microsoft Power Point, therefore the proposed solution is in the form of training to equip vocational school students with the ability to understand Ms. Power Point, this ability is very necessary in completing assignments, organizing the results of interesting material presentations given by school teachers or university lecturers later.